2013
DOI: 10.1021/jm4004076
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Gain of Function and Resistance Mutations in Abl and KIT by Hybrid Compound Design

Abstract: Mutations in the catalytic domain at the gatekeeper position represent the most prominent drug-resistant variants of kinases and significantly impair the efficacy of targeted cancer therapies. Understanding the mechanisms of drug resistance at the molecular and atomic levels will aid in the design and development of inhibitors that have the potential to overcome these resistance mutations. Herein, by introducing adaptive elements into the inhibitor core structure, we undertake the structure-based development o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 51 publications
(91 reference statements)
2
13
0
Order By: Relevance
“…Compound mutations (more than one mutation in a single molecule) have also emerged as a potential driver of acquired resistance to first- and second-generation TKIs, and show different resistance profiles compared with individual mutations, some of them also being resistant to ponatinib, the third-generation TKI able to overcome the negative prognostic impact of the majority of the ABL1 mutations, including the T315I (95). Compound mutations being resistant to ponatinib is still matter of debate: indeed, some authors sustain that compound mutations are always resistant (96, 97), whereas, others have demonstrated that only few combinations are really resistant to ponatinib. In particular, at the last ASH meeting, Soverini et al (98) showed that compound mutations characterize only 3.5% of the chronic phases, 32% of the accelerate/blastic cases and 37% of cases progressed into Ph'-positive acute lymphoblastic leukemia.…”
Section: Next Generation Sequencing (Ngs) and Its Use In CMLmentioning
confidence: 99%
“…Compound mutations (more than one mutation in a single molecule) have also emerged as a potential driver of acquired resistance to first- and second-generation TKIs, and show different resistance profiles compared with individual mutations, some of them also being resistant to ponatinib, the third-generation TKI able to overcome the negative prognostic impact of the majority of the ABL1 mutations, including the T315I (95). Compound mutations being resistant to ponatinib is still matter of debate: indeed, some authors sustain that compound mutations are always resistant (96, 97), whereas, others have demonstrated that only few combinations are really resistant to ponatinib. In particular, at the last ASH meeting, Soverini et al (98) showed that compound mutations characterize only 3.5% of the chronic phases, 32% of the accelerate/blastic cases and 37% of cases progressed into Ph'-positive acute lymphoblastic leukemia.…”
Section: Next Generation Sequencing (Ngs) and Its Use In CMLmentioning
confidence: 99%
“…Several second-generation Bcr-Abl tyrosine kinase inhibitors have been developed to overcome acquired resistance, including dasatinib (Quintás-Cardama et al, 2007;Tokarski et al, 2006), bosutinib (Cortes et al, 2011;Richters et al, 2013), and nilotinib (Boschelli et al, 2001;Damiano et al, 2018) (Figure 1). However, none of these inhibitors can overcome the most difficult Abl T315I mutant.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] In terms of type I/II, this standardization of inhibitors corresponds to ar espective active/inactivec onformational state of the target kinase. [5][6][7] In general, for the regulation of kinase activity,d ifferent conformations and variousm echanisms are known,w hich include cellular translocation, allostericm odulators, or substrate complexation. [4,[8][9][10] However,r egarding the kinome of 518 human kinases, most reversible type I/II ligands, and in particular receptor tyrosine kinase (RTK) inhibitors,a ddress the conservedh inge region and the greaterA TP/substrate binding pocket area.…”
Section: Introductionmentioning
confidence: 99%
“…Although there is actually no uniform agreement, the majority of kinase inhibitors can be categorized into type I–IV binders according to their variable binding modes in kinase proteins (Table ) . In terms of type I/II, this standardization of inhibitors corresponds to a respective active/inactive conformational state of the target kinase . In general, for the regulation of kinase activity, different conformations and various mechanisms are known, which include cellular translocation, allosteric modulators, or substrate complexation .…”
Section: Introductionmentioning
confidence: 99%